Effect of the invasive common reed on the abundance, richness and diversity of birds in freshwater marshes. (28th May 2014) - Gagnon Lupien, N.; Gauthier, G.; Lavoie, C.
Abstract The Eurasian genotype of common reed Phragmites australis subsp. australis is rapidly invading freshwater marshes in North America. Several bird species depend upon particular plant assemblages for feeding and reproduction and could be adversely affected by the expansion of this invader. The objective of this study was to evaluate the effect of common reed on the abundance, richness, diversity and site occupancy of bird assemblages in freshwater marshes recently invaded by the plant (southern Quebec, Canada). We conducted fixed‐distance point counts for songbirds (passerines and rails) and visual surveys for waterbirds (ducks, geese and waders) during two nesting seasons (2009 and 2010). There were major structural differences between common reed stands and marsh vegetation assemblages dominated by other plant species (bulrushes, cattails, sedges). However, there was a little difference in abundance, richness, diversity and site occupancy for songbirds. Marsh wren Cistothorus palustris, a wetland specialist, was the only nesting bird that preferred a native plant (cattail) over common reed, probably because common reed stands have low plant diversity and few appropriate nest materials. No major differences were observed in the abundance of waterbirds between invaded and non‐invaded marshes. For most bird species, the water depth of the marsh had more influence on the abundance of individuals and on site occupancy than the composition of the plant assemblage. Common reed stands can therefore be used by generalist and specialist marsh passerines as feeding and reproduction sites. However, it is possible that in southern Quebec, the number and extent of common reed populations have not yet reached a threshold beyond which adverse effects of the invader on avian species could be significant. This study adds to a growing body of evidence showing that the relationship between invasive plants and birds is not straightforward.